Case studies on the history and use of timber bridges in New Zealand. Issue 3 (27th May 2018) - Singh, Tripti; Page, Dave
ABSTRACT: Wooden bridges have been an important part of road and rail networks in New Zealand. While wooden structures have largely been replaced by concrete and steel on major arteries, they still have a place where lightweight, easily assembled structures are needed. These timber bridges are also an alternative to other materials in roads which carry relatively low traffic loads. In the last 10 years, there has been a resurgence in the installation of engineer-designed wooden structures. Contrary to the traditional method of construction, these prefabricated components are manufactured in a factory and brought to the job site where they can be assembled quickly with a minimum of cutting and drilling. In this document, we summarise the history and use of timber bridges in New Zealand. Most of the older bridges were constructed using Australian hardwood and native durable New Zealand timber. In the 1950s–1960s, preservative-treated timber particularly glue-laminated bridges were built. Currently, few bridges are built entirely from wood. However, in many smaller bridges, the superstructure and decking are built using treated wood. Using some specific case studies based on our historical service test data, we looked at the durability and maintenance requirements of wooden bridges in New Zealand.